Assessment of health implications of violence among secondary school students in Ibadan North Local Government Area of Oyo state, Nigeria (2015)
Children experience violence in their homes schools, and from other children. Often times, they are subjected to violence, in the guise of discipline. This study assessed the health implication of violence among secondary school students in Ibadan North Local government Area of Oyo State, Nigeria. Two research questions were raised and answered. A sample of 500 secondary school students participated in the study. The data collected with Learners Questionnaire (LQ) with reliability coefficient of 0.78 were analysed using descriptive and inferential statistics set at p<0.05 level of significance. The results showed that corporal/physical violence (85%) is the most prevalent violence, followed by sexual violence (64%). The significant implication of violence on the health of students was t-(498), -84.67. It was recommended that efforts should be made to engage health education officials, teachers, students, parents, and community leaders to make the school a healthy place.